Mechanism analysis and performance improvement of mechanized ridge forming of whole plastic film mulched double ridges - Dai, Fei; Song, Xuefeng; Zhao, Wuyun; Shi, Ruijie; Zhang, Fengwei; Zhang, Xuekun (International Journal of Agricultural and Biological Engineering, 2020)
In order to achieve high-performance and mechanization construction standard of whole plastic mulched double ridge seedbed, and to meet its forming process and corresponding agronomic requirements of the mechanized double ridge seedbed, the key working parameters such as the speed of rotary blade group, the thickness of upturned sod and the power consumption of rotary blade group under different parameters were analyzed based on related working performance in ridge forming. Also, the test factors and their range of values were finally determined in this study. Discrete element method (DEM) simulation was applied in the numerical simulation of the mechanized ridge forming process of whole plastic mulched double ridges, and the ridge forming effect and digging resistance variation characteristics of different types of shovels were compared. Taking the forward speed of the combined machine, the penetration angle of the arc-shaped shovel and the depth of rotary tillage as independent variables, and the qualified rate of seedbed tillage as the response value, the mathematical model between the test factors and the qualified rate of the seedbed tillage was established, to explore the influence sequence of the factors on the qualified rate of seedbed tillage, and obtained the following optimal working parameters of the ridge forming device: the advancing velocity of the combined machine of 0.50 m/s, penetration angle of the arc-shaped shovel of 31°, rotary tillage depth of 140 mm, and average qualified rate 95.20% of seedbed tillage in corresponding simulation verification test. Field test showed that the average qualified rate of seedbed tillage in ridge forming device was 93.60%, which was close to that of the simulation results. The actual working condition of the sample machine was basically in line with the simulation process and could relatively precisely reflect the mechanized ridge forming mechanism of whole plastic double ridges. The results showed that the established DEM model and its parameter setting were relatively accurate and reasonable. Keywords: whole plastic film mulched double ridges, mechanized ridge forming, DEM, numerical simulation, parameter optimization DOI: 10.25165/j.ijabe.20201305.5747 Citation: Dai F, Song X F, Zhao W Y, Shi R J, Zhang F W, Zhang X K. Mechanism analysis and performance improvement of mechanized ridge forming of whole plastic film mulched double ridges. Int J Agric & Biol Eng, 2020; 13(5): 107–116.